ASSOCIATION BETWEEN ALOPECIA AREATA AND COVID-19: A SYSTEMATIC REVIEW - Jani Sari Dabukke, Yeyen (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Objective: Alopecia areata (AA) is an inflammatory condition that damages hair cells and causes hair thinning. COVID-19-induced cytokine shift, antigen mimicry between the virus and hair follicles, and COVID-19-induced tissue destruction that revealed autoantigens. This study aims to review the existing literature systematically.Materials and methods: A systematic search strategy was conducted across several electronic reference databases (PubMed, Cochrane Library, ProQuest) and included articles published between 2020–2023. Duplicate publications, review articles, and incomplete articles were excludedResults: Database search yielded a total of 287 articles, which were systematically eliminated, leaving 6 relevant articles. Analyzed articles showed the incidence of alopecia areata (hair loss) in patient post-COVID-19.Conclusion: COVID-19 is a disease that has very wide clinical manifestations. The mechanism of association between COVID-19 and alopecia areata is unclear. However, several factors can also have an effect, such as race, age, and gender.